2020
DOI: 10.6001/energetika.v65i4.4248
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption, capital expenditures, R&D cost and company profitability: evidence from paper and allied industry

Abstract: This paper aims to empirically examine the relations between energy consumption, R&D costs and capital expenditures on the profitability of manufacturing companies in the paper and allied industry. The main focus in this article is on the companies, which are operating in the manufacture of pulp from wood and the paper production industry. Multiple regression analysis was used to test if the energy consumption, R&D costs and capital expenditures significantly predict EBITDA profitability. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Results are in line with existing academic research affirmation that the purpose of investments is to create and exploit opportunities for positive economic rents and that investments allow firms to protect from rivals competitive actions, and reinforce the need for investment decision makers to consider the environment in which the firm is competing, in terms of degree of concentration and investment capacity of competitors, when defining the amount of investment that must be done to achieve and maintain a favorable competitive advantage position. These results are in line with the findings of Tsai and Wang (2004), Zuoza and Pilinkienė (2019), Kim et al. (2021), Peng et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results are in line with existing academic research affirmation that the purpose of investments is to create and exploit opportunities for positive economic rents and that investments allow firms to protect from rivals competitive actions, and reinforce the need for investment decision makers to consider the environment in which the firm is competing, in terms of degree of concentration and investment capacity of competitors, when defining the amount of investment that must be done to achieve and maintain a favorable competitive advantage position. These results are in line with the findings of Tsai and Wang (2004), Zuoza and Pilinkienė (2019), Kim et al. (2021), Peng et al.…”
Section: Discussionsupporting
confidence: 92%
“…and exploit opportunities for positive economic rents and that investments allow firms to protect from rivals competitive actions, and reinforce the need for investment decision makers to consider the environment in which the firm is competing, in terms of degree of concentration and investment capacity of competitors, when defining the amount of investment that must be done to achieve and maintain a favorable competitive advantage position. These results are in line with the findings of Tsai and Wang (2004), Zuoza and Pilinkien_ e (2019), Kim et al (2021), Peng et al (2021), andO'Leary et al (2022), who identified a positive effect of firms' investment on competitive advantage, and also with the findings of Miller et al (2005), Tubbs (2007), Rav selj and Aristovnik (2020), Machokoto et al (2021), who identified that the effects of firm's investment on competitive advantage are contingent on the degree of competition faced by firms, and with the findings of Dias et al (2022), who identified a positive effect of task environment on firm's competitive advantage.…”
Section: Ejmbesupporting
confidence: 93%
See 1 more Smart Citation